Writing the Purpose Statements in Qualitative, Quantitative and Mixed Method Research - Achmad Leofaragusta Kurniawan; Welly Ardiansyah; Nurul Aryanti; Murwani Ujihanti; Wasitoh Meirani (HOLISTICS, 2021)
This paper aims at emphasizing the importance of a purpose statement in a scholarly study. This statement elevates the central idea in a study, and as such it is the most important statement in a research proposal or study. In writing a qualitative purposes statement, a researcher needs to identify a single central phenomenon and to pose a tentative definition for it. The researcher has to employ action words such as “discover,” “develop,” or “understand.” In the process, non-directional language is used, and the inquirer mentions the strategy of inquiry, the participants, and the research site for the study. In a quantitative purpose statement, the researcher mentions the theory being tested as well as the variables and their relationship or comparison. It is important to position the independent variable first and the dependent variable second. The researcher mentions the strategy of inquiry as well as the participant and the research site for the investigation. In some purpose statements, the researcher also defines the key variables used in the study. In a mixed method study, the type of strategy is mentioned as well as a rationale for the type of strategy, such as whether the data are collected concurrently or sequentially. Further, many elements of both good qualitative and quantitative purpose statements are included in the statement. Keywords: Purpose statement, qualitative research, quantitative research, mixed method